'Bedouin Boy With Camel': An Analysis of Archival Photographs of Bedouin Children in Palestine. (2nd January 2023) - Barromi-Perlman, Edna; Kark, Ruth
ABSTRACT: This study analyzes photographs found in historical archives of Bedouin children in Palestine from over a hundred years ago. The Bedouin children were photographed in their natural environment by foreign European photographers touring the Holy Land. Young children were photographed held by their mothers, at work, on a path, or near the tent. The research unravels the context in which the pictures were constructed, documented, and archived. The study explores how colonialist photography in the region generated tropes of presentation of Bedouin children and examines its effects on forms of representation of their childhood of the time. The Bedouin women's inferior status in society and its impact on the documentation of women and children are also examined. The study highlights notions of other children dressing up as 'Hebrew Bedouins' for studio portraiture as part of an orientalist cliché.